The remains of Christopher Columbus in Santo Domingo - López Nuila, Jaime Alberto (Revista de Museología "Kóot", 2018)
The possession of the remains of Christopher Columbus is a matter of honor for Dominicans who claim to hold historically the affection of the discoverer who specifically stated that his remains rest in the Dominican territory. This historical fact is complicated since Spain, for its part, has always wanted to recover the remains of this audacious navigator and discoverer. Spain, which had historically occupied the island, is involved with its nemesis in power, France that assumes control of the entire territory and complicates socio-economic, political and historical mainstream. However, for Spain, it is always a matter of pride and dignity, to recover the remains of such an important character for the kingdom and therefore for history. The bibliographic material used in this article by the author, is an authentic reference, with reliable data on this important historical fact. Revista de Museología "Kóot" No.9 2018: 70-78